Improved generation of human induced pluripotent stem cell-derived cardiac pacemaker cells using novel differentiation protocols - Darche, Fabrice Fernand; Ullrich, Nina D.; Huang, Ziqiang; Koenen, Michael; Rivinius, Rasmus; Frey, Norbert; Schweizer, Patrick Alexander (International journal of molecular sciences, 2022)
Current protocols for the differentiation of human-induced pluripotent stem cells (hiPSC) into cardiomyocytes only generate a small amount of cardiac pacemaker cells. In previous work, we reported the generation of high amounts of cardiac pacemaker cells by co-culturing hiPSC with mouse visceral endoderm-like (END2) cells. However, potential medical applications of cardiac pacemaker cells generated according to this protocol, comprise an incalculable xenogeneic risk. We thus aimed to establish novel protocols maintaining the differentiation efficiency of the END2 cell-based protocol, yet eliminating the use of END2 cells. Three protocols were based on the activation and inhibition of the Wingless/Integrated (Wnt) signaling pathway, supplemented either with retinoic acid and the Wnt activator CHIR99021 (protocol B) or with the NODAL inhibitor SB431542 (protocol C) or with a combination of all three components (protocol D). An additional fourth protocol (protocol E) was used, which was originally developed by the manufacturer STEMCELL Technologies for the differentiation of hiPSC or hESC into atrial cardiomyocytes. All protocols (B, C, D, E) were compared to the END2 cell-based protocol A, serving as reference, in terms of their ability to differentiate hiPSC into cardiac pacemaker cells. Our analysis revealed that protocol E induced upregulation of 12 out of 15 cardiac pacemaker-specific genes. For comparison, reference protocol A upregulated 11, while protocols B, C and D upregulated 9, 10 and 8 cardiac pacemaker-specific genes, respectively. Cells differentiated according to protocol E displayed intense fluorescence signals of cardiac pacemaker-specific markers and showed excellent rate responsiveness to adrenergic and cholinergic stimulation. In conclusion, we characterized four novel and END2 cell-independent protocols for the differentiation of hiPSC into cardiac pacemaker cells, of which protocol E was the most efficient.
Gesehen am 06.07.2023